Aristotle on definition - Deslauriers, Marguerite, 1956- (Philosophia antiqua, 2007)
This book argues that Aristotle offers us a consistent theory of definition, according to which a particular type of definition - one which states the formal cause of a simple item - is fundamental. It begins by considering definitions as indemonstrable first principles in demonstrations, and inquires how such definitions can have the certainty required by that role. Later chapters look to the Metaphysics to understand how the unity of definitions guarantees their certainty, and to the Topics to discover why definitions must be formulated in terms of the genus and differentia(e) of the object defined. This work contributes to our understanding of the connection between the function of definition in demonstration and its character as a statement of essence.